2018
DOI: 10.1111/pim.12519
|View full text |Cite
|
Sign up to set email alerts
|

Leishmania amazonensis induces modulation of costimulatory and surface marker molecules in human macrophages

Abstract: Manipulation of costimulatory and surface molecules that shape the extent of immune responses by Leishmania is suggested as one of the mechanisms of evading the host's defences. The experiments reported here were designed to evaluate the expressions of CD11b, CD11c, CD14, CD18, CD54, CD80, CD86, CD206, MHC class II and TLR-2 (Toll-like receptor 2) in human macrophages infected with L. amazonensis. Phenotypic evaluation revealed a negative modulation in CD11b, CD11c, CD14, CD18, CD54 and MHC class II molecules,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Changes in abundance of the integrin subunit Itgβ5 (O70309, r 1 = 0.73 and r 2 =0.55) which acts with Itga5 as a fibronectin receptor, were detected, as well as differences in other adhesion or adhesion signaling molecules (Nisch/Q80TM9, r 1 =0.66, r 2 =0.56; Plxna1/ P70206, r 1 = 1.65, r 2 =2.46; Lpxn/Q99N69, r 1 = 0.74, r 2 =0.65) ( Table 1 and Table 2 ). Thus, our data expand and further emphasise the impact of intracellular Leishmania infection on connective tissue remodeling that may modify host adaptive immune responses mediated by infected macrophages [110, 111].…”
Section: Resultsmentioning
confidence: 60%
“…Changes in abundance of the integrin subunit Itgβ5 (O70309, r 1 = 0.73 and r 2 =0.55) which acts with Itga5 as a fibronectin receptor, were detected, as well as differences in other adhesion or adhesion signaling molecules (Nisch/Q80TM9, r 1 =0.66, r 2 =0.56; Plxna1/ P70206, r 1 = 1.65, r 2 =2.46; Lpxn/Q99N69, r 1 = 0.74, r 2 =0.65) ( Table 1 and Table 2 ). Thus, our data expand and further emphasise the impact of intracellular Leishmania infection on connective tissue remodeling that may modify host adaptive immune responses mediated by infected macrophages [110, 111].…”
Section: Resultsmentioning
confidence: 60%
“…Interestingly, after contact with the parasite, EVs released by B‐1 cells showed decreased expression of these molecules, suggesting that the parasite could modulate the sorting of MHC class II to the vesicles. Previous studies have shown that L. amazonensis modulates the expression of MHC II molecules by reducing their expression in murine and human macrophages infected with promastigotes 48,49 . The MHC II molecules were found to be associated with the parasites very early after they are phagocytosed, but these molecules were not detected after 48 h of infection 49 .…”
Section: Discussionmentioning
confidence: 93%
“…42,43 Depend- macrophages infected with promastigotes. 48,49 The MHC II molecules were found to be associated with the parasites very early after they are phagocytosed, but these molecules were not detected after 48 h of infection. 49 This time coincides with the increase in the protease activity of the parasite, suggesting that the parasite could internalize and very likely degrade host MHC II molecules.…”
Section: Discussionmentioning
confidence: 99%
“…MHC and co-stimulatory molecules are important signals required by T cells to be activated, and down-modulation of these molecules is an escape mechanism of the immune response. Actually, it was already shown that L. amazonensis and L. mexicana amastigotes inside the parasitophorous vacuole degrade MHC class II molecules (De Souza Leao et al, 1995;Antoine et al, 1999;Costa et al, 2018), without affecting CD86 expression (Costa et al, 2018). Nevertheless, a study in canine peripheral blood monocyte-derived macrophages showed an upregulation of MHC molecules in cells infected with L. infantum in the presence of T cells in vitro (Diaz et al, 2012).…”
Section: Discussionmentioning
confidence: 98%